Downregulated miR-18a and miR-92a synergistically suppress non-small cell lung cancer via targeting Sprouty 4. Issue 4 (1st April 2022) - Zhang, Xinju; Wang, Xianyi; Chai, Binshu; Wu, Zong; Liu, Xiaomin; Zou, Heng; Hua, Ziyi; Ma, Zhongliang; Wang, Weiwei
ABSTRACT: As a novel noncoding RNA cluster, miR-17-92 cluster include six members: miR-17, miR-18a, miR-19a, miR-19b-1, miR-20a, and miR-92a. Dysregulation of miR-17-92 has been proved to be connected with the advancement of a series of human diseases, but the roles of miR-17-92 cluster in non-small cell lung cancer (NSCLC) have not been absolutely elaborated. Herein, we determined that miR-17-92 cluster were upregulated significantly in NSCLC tissues, and the cell proliferation, migration and cycle progression of NSCLC were also facilitated under the function of miR-17-92 cluster. Sprouty 4 ( SPRY4 ) was a direct target of miR-92a, and its overexpression restrained the exacerbation of NSCLC induced by miR-92a. Furthermore, the tumor xenograft assay showed that miR-92a facilitated tumor growth by inhibiting the expression of SPRY4 and mediating Epithelial-Mesenchymal Transition (EMT) in vivo . Finally, we looked into the synergistic effects of miR-92a and miR-18a on NSCLC, and found that antagomiR-18a treatment arrested the tumor growth rate of xenografted mice markedly. GRAPHICAL ABSTRACT: uf0001